Influence of entrepreneurial characteristics towards the growth of startups. (9th September 2021) - Anitha, N.; Sathish, P.; Ravinagarajan, Janani
India has the second largest startup ecosystem with the growth rate of 10-12% with 20, 000 startups. The factors that make India appealing are cost of doing business, proximity and size of the market. 55% of the college graduates prefer to work in startups over corporates especially in Bangalore the top startup destinations with over 65% of the total Indian startups also been listed in the world's 20 leading startup cities in the 2015. When talking about the growth of startup success, the other end question is what factors influence and trigger entrepreneurial success whether prevailing entrepreneurial ecosystem or a personality trait of an entrepreneur. Extensive literature since 2000 highlights much about the personality traits. Hence, this study focuses on the personality traits like self-efficacy, innovativeness, locus of control, risk attitude and the need for achievement and also analyse the extent to which each characteristic is contributing towards entrepreneurship performance outcomes. The data were obtained from 98 startups in Bangalore city through survey and necessary analysis done to meet the objectives.